Undergraduate Students’ Attitudes Towards Volunteer Work – Survey of Students of King Abdulaziz University – - Al-Zebali, Wael Ali (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the main components of the attitude that the student has throughout his university studies which motivate the student to practice volunteer work. The researcher used the descriptive approach which is to describe and analyze data derived from the research sample of 410 students from King Abdelaziz University- Faculty of Arts and Humanities, using the social survey method and the questionnaire tool based on Likert scale methodology. The most important results of the study were first: There is awareness among Undergraduate students of the concept of volunteer work by 67.6%, second: The undergraduate student’s feeling towards volunteer work drives him towards helping others by 90.7%, third: University student participation in volunteer work has emerged in volunteering in the area of ​​specialization by 61.2%, fourth: One of the most important obstacles that limit the undergraduate student's participation in volunteer work is that the advertising for volunteer work is weak by 70% and fifth: One of the most important proposals to enhance the undergraduate student's attitudes towards volunteer work is to work with individuals who specialize in volunteer work by 87.6%.
Keywords: volunteer work; obstacles to volunteering; volunteering; volunteering trends